Analisis Risiko Konstruksi pada Proyek Perumahan Bersubsidi di Wilayah Jawa Timur Ditinjau Dari Pihak Kontraktor - Dean Dara Oktaviani; Suryawan Murtiadi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The construction of subsidised housing in East Java is one of the government's main focuses in its efforts to improve public access to decent housing. Contractors play a role in the construction of subsidised housing by analysing potential construction risks. This study aims to identify, evaluate, and propose construction risk mitigation in subsidised housing projects from the contractor's perspective using the Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods. Risk identification using the FMEA approach is applied to analyse the potential for risks to occurrence, the severity of risks, and the detection of risks, as well as to determine risk priorities based on the Risk Priority Number (RPN). Data and questionnaires from 43 correspondents were collected through interviews with project participants, field observations, form filling and project document studies. Questionnaire assessments were conducted on 39 basic risk indicator variables, with a weighting of 4,64% for delayed payments. Delays in material procurement were 4,54%, equipment risk due to loss of tools at the project site was 4,37%, method and construction technique risk due to design changes by the project owner that altered work methods and implementation was 4,19%, and labour risk due to labour shortages was 4,10%. Decision-making mitigation measures include changing the form of work orders, regarding the implementation schedule and payment period, procuring logistics warehouses for tools and materials, and recruiting new personnel. The recommendations provided include more detailed planning, strict supervision of the supply chain, and intensive coordination with stakeholders.